Clinical aspects of neurocysticercosis in children - Morales, Nı́vea M.O.; Agapejev, Svetlana; Morales, Rogério R.; Padula, Niúra A.M.R.; Lima, Márcia M.F. (Elsevier, 2000)
The purpose of this report was to evaluate the clinical aspects of neurocysticercosis in children from a Brazilian region. A retrospective study of 25 children with this neuroparasitosis was performed. The diagnosis was based on clinical, cerebrospinal fluid, and neuroimaging findings. The patients were predominantly male (72%), were 1 to 11 years of age (average = 8 years, 6 months), and most resided in urban areas (68%). The more frequent manifestations were epileptic seizures (72%), headache (60%), learning disability (24%), behavioral changes (12%), psychomotor involution (8%), and intracranial hypertension (4%). The neurologic examination was normal in 80% of the patients. Twenty-two children received only symptomatic drugs. Three patients underwent treatment with cysticidal drugs, one with praziquantel and two with albendazole, with complete remission of the signs in one patient (33%) and improvement in two others (67%). Of the 25 patients, 43.4% had remission and 47.8% had improvement. We emphasize the need to consider neurocysticercosis as a differential diagnosis in children coming from endemic areas and presenting with learning disabilities, behavioral changes, and psychomotor involution. The clinical aspects in most of the children from the Botucatu region suggest a spontaneous resolution of neurocysticercosis without the need for cysticidal treatment. © 2000 Elsevier Science Inc.